2015
DOI: 10.7448/ias.18.1.19470
|View full text |Cite
|
Sign up to set email alerts
|

Anogenital HIV RNA in Thai men who have sex with men in Bangkok during acute HIV infection and after randomization to standard vs. intensified antiretroviral regimens

Abstract: IntroductionHIV transmission risk is highest during acute HIV infection (AHI). We evaluated HIV RNA in the anogenital compartment in men who have sex with men (MSM) during AHI and compared time to undetectable HIV RNA after three-drug versus five-drug antiretroviral therapy (ART) to understand risk for onward HIV transmission.MethodsMSM with AHI (n=54) had blood, seminal plasma and anal lavage collected for HIV RNA at baseline, days 3 and 7, and weeks 2, 4, 12 and 24. Data were compared between AHI stages: 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…In the current study, the undetectable seminal viral load we found after ART may be attributable to the relatively longer duration of ART, which differs from our previous study with only 6 months of ART . Our result is consistent with those of previous studies for 6 months or more than 3 years of ART . Further studies are still needed to confirm our results in more patients receiving prolonged ART and over more intervals.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, the undetectable seminal viral load we found after ART may be attributable to the relatively longer duration of ART, which differs from our previous study with only 6 months of ART . Our result is consistent with those of previous studies for 6 months or more than 3 years of ART . Further studies are still needed to confirm our results in more patients receiving prolonged ART and over more intervals.…”
Section: Discussionsupporting
confidence: 81%
“…Here we include data from the 88 MSM enrolled and treated with immediate ART, all of whom had reached beyond 24 weeks on study at time of analysis. Clinical, immunological and virological characteristics of the study participants are primary endpoints and have been described in several publications [27][28][29][30][31][32]. The study also collects descriptive data of demographics and behavioural risk, and characteristics of sexual contacts.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of cART initiated during PHI on HIV genital shedding has rarely been studied [1517], and there are no data on the genital HIV reservoir at this stage. cART initiated during PHI may not have the same impact as cART initiated in the chronic phase [18].…”
Section: Introductionmentioning
confidence: 99%